E04 Effects of unstable load vs stable load on muscle activation and bar velocity during a bench press - Crosbie, Lewis; Langdon, Dominic; Thompson, Nathan (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Unstable load (UL) resistance exercises have gained popularity due to the potential to increase strength and neural development compared to traditional resistance exercises (Costello, 2022, J Strength Cond Res, 36, 881-887). It is assumed that training with an UL will increase the recruitment and activation of stabilising muscles, which is beneficial for daily activities and sport performance Kohler et al. (2010, J Strength Cond Res, 24, 313-321). Despite the recent increase in popularity, there is a limited amount of research that has been conducted using a UL and its impact on primary mover muscle activity. The purpose of this study was to investigate if a UL increases muscle activity of primary movers (pectoralis major sternocostal head [PEC] and triceps brachii long head [TRI]) during a bench press compared to a stable load (SL), measured via a Biopac electromyography (EMG) device. Additionally, bar velocity (m/s) using a GymAware device was compared between both UL and SL conditions. Following ethical approval, thirteen resistance-trained males were recruited (age = 21 ± 2 years; height = 178 ± 3 cm; mass = 79 ± 12 kg). Participants attended a familiarisation session, where 1RM and EMG maximum voluntary contraction (MVC) were determined. Following this, participants took part in a randomized crossover design at pre-determined loads. For the SL trial, participants performed 3 sets of 8 repetitions at 65% 1RM using a standard Olympic barbell. The US trial followed an identical protocol; however, an earthquake bar was loaded with 50% 1RM. The two-way repeated measures ANOVA revealed a significant interaction effect for the PEC activation, where there was an increase during UL but not SL condition (P = 0.001, ŋ2 = 0.633). No difference was found in the TRI between conditions (P > 0.05). There was a significant 17% loss in velocity in the UL condition (P = 0.022, ŋ2 = 0.273). A significant difference was revealed in the eccentric phase for the UL condition (P = 0.001, ŋ2 = 0.473). In conclusion, muscle activation was increased in the pectoralis major muscle during the UL compared to SL resistance training. There was also an increase in velocity loss during the UL. In addition, the time of the eccentric phase was significantly longer during the UL condition. Therefore, despite the reduction in intensity, a UL may elicit greater activation of primary movers when compared to traditional resistance training alone.